The effect of niobium on the adhesive wear resistance of ferritic stainless steel - Aksoy, M.; Yilmaz, S. O.; Evin, E. (Sage Publications Ltd, 2009)
The effects of Nb and homogenization heat treatment on the adhesive wear resistance of AISI 430 ferritic stainless steels containing 18 wt% Cr were investigated. The samples were cast as having additionally 0.5, 1.0, 1.5, and 3 wt% Nb. The samples were hot forged in the form of bars having 20 mm in diameters, and the samples were homogenized. The dry sliding wear tests were performed against AISI 1050 steel in a block-on-ring apparatus under the loads of 40, 60, and 80 N, respectively. The relations between wear rate, sliding distance, surface hardness, notch toughness, grain boundary energies, and friction coefficient were detected, and these relations were searched through metallographic investigations. Finally, it was seen that homogenization heat treatment reduced the total wear rate. The least wear rate was obtained from the homogenized sample having 0.5 wt% Nb in which niobium demonstrated a tendency to stabilize the cubic MX-type precipitates. A compatible relation between surface hardness, notch toughness, grain boundary energies, friction coefficient, and total wear rate was detected for homogenized samples.
Keywords: ferritic stainless steels; adhesive wear